A study of the intermolecular interactions of lipid components from analogue fingerprint residues - Johnston, Andrew; Rogers, Keith (Elsevier, 2017)
A compositionally simplified analogue of a latent fingermark was created by combining single representatives of each major component of a natural fingermark. Further modified analogues were also produced each having one component removed. The aim of this study was to investigate the intermolecular interactions that occurred within these analogue samples using Fourier Transform Infrared (FT-IR) Microspectroscopy. FT-IR microspectroscopy showed that the absence of squalene and cholesterol significantly restricted the interactions between the other organic constituents within the analogue samples. Investigating the intermolecular interactions of organic compounds within a simplified analogue solution could indicate corresponding interactions that occur within natural fingermarks. These potential interactions could go on to be the target of further investigation of latent fingermark chemistry, and ultimately contribute to a better understanding of the aging processes and degradation mechanisms that take place post-deposition.